Detecção molecular de Brucella sp. em leite “informal” comercializado nos municípios de Alagoas - Portela, Otto Cabral (2016)
The objective of this study to detect the informal trade in bovine milk, milk “in natura" in the state of Alagoas and the presence of Brucella sp. by Polymerase Chain Reaction (PCR) in real time. A survey of cities that held informal milk trade with the acquisition of samples of the product marketed in the presentation of the sale was realized. The obtained milk was kept and transported under refrigeration to the laboratory, then the samples were homogenized and withdrawal rates of 50 mL packaged in FALCON tubes, properly identified and frozen, to be processed at the Laboratory of Infectious of Domestic Animal Diseases, University Federal Rural de Pernambuco. It was found 100 outlets in 80 cities in the state of Alagoas. With DNA extraction and PCR analysis detected the presence of Brucella sp. of the samples in 1% (1/100) from analysis descriptive statistics for convenience. It is concluded from this study that there is illegal trade in milk in Alagoas and the presence of Brucella sp. in bovine milk, which can pose a potential risk of transmission of brucellosis to the population that consumes the milk marketed informally.